Novel evolutionary lineages revealed in the Chaetothyriales (fungi) based on multigene phylogenetic analyses and comparison of its secondary structure - Réblová, Martina; Untereiner, Wendy A; Réblová, Kamila (PloS one, 2013)
Cyphellophora and Phialophora (Chaetothyriales, Pezizomycota) comprise species known from skin infections of humans and animals and from a variety of environmental sources. These fungi were studied based on the comparison of cultural and morphological features and phylogenetic analyses of five nuclear loci, i.e., internal transcribed spacer rDNA operon (ITS), large and small subunit nuclear ribosomal DNA (nuc28S rDNA, nuc18S rDNA), β-tubulin, DNA replication licensing factor (mcm7) and second largest subunit of RNA polymerase II (rpb2). Phylogenetic results were supported by comparative analysis of ITS1 and ITS2 secondary structure of representatives of the Chaetothyriales and the identification of substitutions among the taxa analyzed. Base pairs with non-conserved, co-evolving nucleotides that maintain base pairing in the RNA transcript and unique evolutionary motifs in the ITS2 that characterize whole clades or individual taxa were mapped on predicted secondary structure models. Morphological characteristics, structural data and phylogenetic analyses of three datasets, i.e., ITS, ITS-β-tubulin and 28S-18S-rpb2-mcm7, define a robust clade containing eight species of Cyphellophora (including the type) and six species of Phialophora. These taxa are now accommodated in the Cyphellophoraceae, a novel evolutionary lineage within the Chaetothyriales. Cyphellophora is emended and expanded to encompass species with both septate and nonseptate conidia formed on discrete, intercalary, terminal or lateral phialides. Six new combinations in Cyphellophora are proposed and a dichotomous key to species accepted in the genus is provided. Cyphellophora eugeniae and C. hylomeconis, which grouped in the Chaetothyriaceae, represent another novel lineage and are introduced as the type species of separate genera.
Keywords: Tubulin; Genetic Loci; Base Sequence; Ascomycota; RNA ribozomální; Genes, Fungal; Molecular Sequence Data; Nucleic Acid Conformation; Evolution, Molecular; molekulární evoluce; mezerníky ribozomální DNA; konformace nukleové kyseliny; Phylogeny; RNA, Ribosomal; geny hub; tubulin; molekulární sekvence - údaje; nukleotidové motivy; konsenzuální sekvence; Consensus Sequence; sekvence nukleotidů; Spores, Fungal; Nucleotide Motifs; DNA, Ribosomal Spacer; fylogeneze; spory hub; genetické lokusy